Biography, science studies and the historiography of archaeological research: Managing personal archives - Kaeser, Marc Antoine (Complutum, 2013)
This paper examines the potential of biographical studies for the history of archaeology. In particular, I seek to demonstrate that personal archives may be a valuable source for the historiography of archaeological research. First, they allow the identification of practical interactions between science and society. Second, personal archives allow us to underscore the epistemological interference between the discussion of archaeological topics and certain scientific debates, which has traditionally been overlooked by historians of archaeology. Third, I argue that biography and the use of personal archives may well contribute to reconciliation between critical approaches inspired by science studies and the more traditional history of ideas. Simultaneously, they compel historians of archaeology to broaden their perspectives to the history of science in general in order to consider the origins of the present discipline in the context of past configurations of knowledge and research.